2023
DOI: 10.1101/2023.05.22.541664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditional control of universal CAR T cells by cleavable OFF-switch adaptors

Abstract: As living drugs, engineered T cell therapies are revolutionizing disease treatment with their unique functional capabilities. However, they suffer from limitations of potentially unpredictable behavior, toxicities, and non-traditional pharmacokinetics. Engineering conditional control mechanisms responsive to tractable stimuli such as small molecules or light is thus highly desirable. We and others previously developed universal chimeric antigen receptors (CARs) that interact with co-administered antibody adapt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“… 12 , 13 By creating a library of molecular adapters, a T cell engineered with a single universal SAR can be directed against multiple tumor targets and tailored to the antigenic repertoire of the tumor, thereby reducing the need for multiple engineering runs to produce T cells with distinct antigen specificity. Pre-clinical studies have confirmed the utility of this strategy in the treatment of hematologic and solid tumor models using a variety of donor moieties 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and the approach is currently being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“… 12 , 13 By creating a library of molecular adapters, a T cell engineered with a single universal SAR can be directed against multiple tumor targets and tailored to the antigenic repertoire of the tumor, thereby reducing the need for multiple engineering runs to produce T cells with distinct antigen specificity. Pre-clinical studies have confirmed the utility of this strategy in the treatment of hematologic and solid tumor models using a variety of donor moieties 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 and the approach is currently being tested in clinical trials.…”
Section: Introductionmentioning
confidence: 94%
“…Numerous molecular adapter approaches have been evaluated for templating ternary complexes that bridge universal CARs with tumor antigens. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Bifunctional small molecule adapters are attractive tools for directing universal CARs due to their ease of production, high tumor penetrance, and low immunogenicity. We reasoned that covalent attachment of the small molecule adapter to a universal receptor could enhance functionality of the receptor.…”
Section: Introductionmentioning
confidence: 99%